2009
DOI: 10.1243/13506501jet480
|View full text |Cite
|
Sign up to set email alerts
|

Wear tests of orthopaedic biopolymers with the biolubricant augmented by a visco-supplement

Abstract: The lubricant in which both natural and replacement joints must operate is synovial fluid. In vitro wear tests of such prostheses and their biomaterials generally employ a lubricant based on bovine serum, as this contains proteins that have a critical impact in reproducing clinically valid wear rates in the laboratory. However, it is also recognised that bovine serum is not identical to synovial fluid, a key difference being that synovial fluid includes hyaluronic acid but bovine serum does not. Few clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Previous pin-on-plate studies using bovine serum as the lubricant have also shown this pattern of little change in the S a values and it was suggested that these surface roughness results indicated that there was no transfer film on the plate surface [27,28,31]. As the S a remains similar for the duration of the wear test, this means that there was little change to the average roughness of the plates.…”
Section: Surface Roughness Analysismentioning
confidence: 72%
See 4 more Smart Citations
“…Previous pin-on-plate studies using bovine serum as the lubricant have also shown this pattern of little change in the S a values and it was suggested that these surface roughness results indicated that there was no transfer film on the plate surface [27,28,31]. As the S a remains similar for the duration of the wear test, this means that there was little change to the average roughness of the plates.…”
Section: Surface Roughness Analysismentioning
confidence: 72%
“…This can be compared to the wear factors of 1.1 × 10 −6 mm 3 /Nm and 1.6 × 10 −6 mm 3 /Nm when using dilute bovine serum as the lubricant in the same rig [27,28]. For failed and explanted Charnley hips, the wear factor has been found to be 2.1 × 10 −6 mm 3 /Nm [29].…”
Section: Wear Resultsmentioning
confidence: 99%
See 3 more Smart Citations